1999
DOI: 10.1103/physrevlett.82.5261
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Electron-Beam Bunch Length and Emittance Using Shot-Noise-Driven Fluctuations in Incoherent Radiation

Abstract: Longitudinal and transverse phase space information has been obtained from a statistical analysis of fluctuations in the radiation spectrum of an electron bunch. Uncorrelated shot noise fluctuations in longitudinal beam density result in incoherent radiation with a spectrum that consists of spikes, with width inversely proportional to the bunch length. Measurements were performed at l 620 nm on a 1 -5 ps long, 44 MeV bunch propagating through a wiggler. Bunch length and emittance obtained with this single shot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 10 publications
0
50
0
Order By: Relevance
“…As predicted, the measured spectra of single FEL pulses contain approximately N peaks, although their positions and intensities vary [11,12]. Furthermore, it has been shown that the latter finding is a general property of pulsed radiation which is not depending on laser operation [14].…”
Section: Multiple Coherent Componentsmentioning
confidence: 84%
“…As predicted, the measured spectra of single FEL pulses contain approximately N peaks, although their positions and intensities vary [11,12]. Furthermore, it has been shown that the latter finding is a general property of pulsed radiation which is not depending on laser operation [14].…”
Section: Multiple Coherent Componentsmentioning
confidence: 84%
“…In the visible range, narrow band of the off -axis radiation from the undulator was used for electron beam energy spread, alignment and emittance characterization [33]. The single -shot fluctuation spectrum was used for the electron beam bunch length measurement [34]. Most single-pass high gain FEL undulators are made up by several segments, each segment length is on the order of 2 to 5 meters.…”
Section: Beam Diagnostics For the Undulatormentioning
confidence: 99%
“…Average properties of the output were studied in [10][11][12][13][14][15][16] and fluctuations were considered in [17][18][19][20]. The spiking of the output radiation (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of high-gain single-pass free-electron lasers has been developing since the late 1970's [6][7][8][9]. Because SASE starts from the shot noise in the electron beam, a proper theory requires a statistical treatment of the output radiation [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%